The Role of Active and Passive Smoking in Chronic Obstructive Pulmonary Disease and Systemic Inflammation: A 12-year Prospective Study in China - Chen, L; Xiong, H; Wen, Q; Lv, J; Sun, D; Pei, P; Yang, L; Chen, Y; Du, H; Li, L; Yang, X; Avery, D; et al. (Springer Netherlands, 2024)
Background: There is no consensus on the cause and effect of systemic chronic inflammation (SCI) regarding chronic obstructive pulmonary disease (COPD). The impact of second-hand smoke (SHS) on COPD has reached inconsistent conclusions. Methods: The China Kadoorie Biobank cohort was followed up from the 2004–08 baseline survey to 31 December 2018. Among the selected 445,523 participants in the final analysis, Cox and linear regressions were performed to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) of tobacco exposure with COPD risk and baseline levels of log-transformed inflammatory factors [βs (95% CIs)], respectively. Results: Participants were followed up for a median of 12.1 years and 11,825 incident COPD events were documented. Ever-smokers were associated with a higher risk of COPD than non-smokers with non-weekly SHS exposure. A younger age to start smoking, a greater amount of daily tobacco consumption, and deeper inhalation were associated with increased risk of COPD and correlated with elevated levels of plasma high-sensitivity C-reactive protein (hs-CRP, all Ptrend < 0.001) even two years before COPD onset. Among former smokers, COPD risk declined with longer smoking cessation (Ptrend < 0.001) and those quitting smoking for over ten years presented no difference in COPD risk and hs-CRP level from non-smokers [HR (95% CI) = 1.05 (0.89, 1.25), β (95% CI) = 0.17 (− 0.09, 0.43)]. Among non-smokers, weekly SHS exposure was associated with a slightly higher COPD risk [HR (95% CI) = 1.06 (1.01, 1.12)]. Conclusions: Incremental exposure to tobacco smoke was related to elevated SCI level before COPD onset, then an increase in COPD susceptibility. Quitting smoking as early as possible is suggested as a practical approach to reducing COPD risk in smokers. Given the high prevalence of both COPD and SHS exposure, the risk associated with SHS exposure deserves attention.